2012
DOI: 10.1007/10091_2012_12
|View full text |Cite
|
Sign up to set email alerts
|

Solitons in a Parametrically Driven Damped Discrete Nonlinear Schrödinger Equation

Abstract: We consider a parametrically driven damped discrete nonlinear Schrödinger (PDDNLS) equation. Analytical and numerical calculations are performed to determine the existence and stability of fundamental discrete bright solitons. We show that there are two types of onsite discrete soliton, namely onsite type I and II. We also show that there are four types of intersite discrete soliton, called intersite type I, II, III, and IV, where the last two types are essentially the same, due to symmetry. Onsite and intersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In our first simulation, we consider the fundamental site-centred discrete soliton of the dNLS equation, that has been considered before in, e.g., [9,10,11,12]. Such solutions will satisfy (3) with Ȧj = 0 and can be obtained rather straightforwardly using Newton's method.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our first simulation, we consider the fundamental site-centred discrete soliton of the dNLS equation, that has been considered before in, e.g., [9,10,11,12]. Such solutions will satisfy (3) with Ȧj = 0 and can be obtained rather straightforwardly using Newton's method.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The parametrically driven dNLS equation (3) was studied in [10,11], where it was shown that the parametric drive can change the stability of fundamental discrete solitons, i.e., it can destroy onsite solitons as well as restore the stability of intersite discrete solitons, both for bright and dark cases. In [12], breathers of (3), i.e., spatially localised solutions with periodically time varying |A j (τ )| emanating from Hopf bifurcations, were studied systematically.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the stability of discrete solitons in the parametrically driven DNLS equations, both conservative and dissipative ones, has been studied in Refs. [74][75][76][77][78].…”
Section: Introductionmentioning
confidence: 99%